Measuring the Effects of Reading Assistance Dogs on Reading Ability and Attitudes in Elementary Schoolchildren. Issue 2 (2nd April 2016) - Lenihan, Dawn; McCobb, Emily; Diurba, Amanda; Linder, Deborah; Freeman, Lisa
ABSTRACT: Reading assistance dogs can be incorporated into reading programs to increase a child's desire and ability to read. However, more data is needed to demonstrate the effectiveness of such programs. A 5-week reading assistance dog program was implemented to assess feasibility and effectiveness. Participants included 18 children entering the 2nd grade (nine assigned to read to dogs and nine assigned to read without dogs present). Fifteen children completed the study (nine in the dog group and six in the control group; p = .058). To detect changes in reading ability and in attitudes toward reading, a Curriculum Based Measurement (CBM) for reading and an Elementary Reading Attitude Survey (ERAS) was given at Week 0 and Week 5. There were no significant differences over the course of the study in ERAS scores for the dog group, but the control group had significant reductions in the ERAS academic score ( p =.04). There was a numerically larger but not statistically different reduction in CBM in the control group compared to the dog group ( p = .16). Further studies are warranted to determine if these trends represent statistically significant effects of reading assistance dog programs.